The costs of recruiting apprentices: Evidence from German workplace-level data. (May 2017) - Wenzelmann, Felix; Muehlemann, Samuel; Pfeifer, Harald
In this article, we use workplace-level data to analyse the costs of filling an apprenticeship vacancy in Germany. We find that such recruitment costs amount on average to €600 per hire (almost one month's pay of an apprentice or approximately 1–2 % of a workplace's training expenditures), but costs are heterogeneous across workplaces and vary strongly by training occupation. Our results suggest that a high degree of competition among training workplaces in the region is associated with an increase in recruitment costs. Furthermore, we find that workplaces with a works council or an investment-oriented training strategy incur higher recruitment costs. Our results are important in light of the increasing competition for talented school leavers induced by demographic change.